METALANGUAGE MODELS OF POLITICAL SCIENCE (American Journal of Interdisciplinary Research and Development, 2022)
The axiom of letter and symbol is based on two fundamental meta-models of political science. The letter structure dominated the science until the early 1920s, defining the boundaries of “science” in the name of consciousness. Despite the contradictions between the principles of learning the letter and the symbol, in the political discourse these principles are complementary, that is, principles that complement each other’s constructive, methodological shortcomings. This article scrutinizes the principles on which the theoretical metalanguage models that determine the structure of political science discourse are based and derived from the specificity of the letter and symbol